(untitled) (American Journal of Islam and Society, 2017)
The following study envisions the modern history of the Palestinian- Israeli conflict through the application of previously underutilized theoretical frames. Beginning with the unprecedented political and social upheaval wrought upon the Middle East after the end of World War I, the article unfolds in three distinct sections. The first section provides an historical introduction to the global, transnational forces that guided the developing infrastructure of political conflict within the region. The second section articulates the ideological parameters of the international political and economic forces (“neoliberalism”) that connect the past and present of political conflict in the region as well as the local (state and non-state) and non-local actors involved in its contemporary manifestation. The third and final section reconceptualizes the Palestinian-Israeli conflict not exclusively as a territorial dispute or as a nebulous clash of cultures, but rather as a deliberate, operational casualty enduring in the service of an aggressive, transnational, and indeed historical force whose trajectory spans the length of the twentieth and early twenty-first centuries: neoliberalism. In each sphere in which the neoliberal ideal has been applied – one, an historical fait accompli, another, a contemporary situation en cours – an important, connective element persists: the distinctly non-local origin of both the historical forces and the contemporary economic manifestations under examination.